The copywriting sourcebook how to write better copy, faster : for everything from ads to websites - Maslen, Andy (Marshall Cavendish Business, 2010)
It's OK knowing the theory, but when it's 9am and you have just been given until lunchtime to write some copy for a new sales email, landing page, press ad or brochure, what you really need is a shortcut